Protection by different classes of dietary polyphenols against palmitic acid-induced steatosis, nitro-oxidative stress and endoplasmic reticulum stress in HepG2 hepatocytes. (May 2018) - Rafiei, Hossein; Omidian, Kosar; Bandy, Brian
Graphical abstract: Increased load of electron donors (NADH and FADH2 ) originating from fat metabolism to the mitochondrial electron transport chain (ETC) results in increased ROS production due to leakage of electrons from complex I and III. These ROS further cause mitochondrial dysfunction and decrease mitochondrial content. Polyphenols improve the flow of electrons in the ETC possibly by inducing the expression of mitochondrial respiratory complex subunits and improving mitochondrial function leading to protection against the decline in mitochondrial membrane potential. Polyphenols also prevent induction of endoplasmic reticulum chaperones by palmitate, leading to lower expression of pro-apoptotic CHOP . By preventing the decline in ΔΨm and the expression of ER stress chaperones and CHOP, polyphenols may prevent apoptosis involved in the progression of NAFLD. Highlights: Palmitate increased hepatocyte ROS, mitochondrial dysfunction and ER stress. Functional food-relevant polyphenols all prevented steatosis and decreased intracellular ROS. Polyphenols prevented a large increase in iNOS mRNA expression. Some polyphenols helped preserve mitochondrial content and membrane potential. Quercetin most effectively attenuated ER stress. Abstract: Polyphenol-rich functional foods have shown promise in ameliorating NAFLD but the relative effectiveness and mechanisms of different polyphenols are largely unknown. In a model of steatosis using HepG2 hepatocytes exposed to palmitic acid, we investigated the effect of selected polyphenols (resveratrol, quercetin, catechin, cyanidin, kuromanin) and berberine. Exposure to palmitic acid produced steatosis and intracellular ROS production, which were prevented by all of the polyphenols and berberine, at 10 µM. Palmitic acid produced a 245% increase in mRNA for inducible nitric oxide synthase ( iNOS ) that was almost completely prevented by all of the polyphenols (but not by berberine). Most of the polyphenols also partially inhibited palmitic acid-induced increases in markers of endoplasmic reticulum stress, and decreases in mitochondrial content and mitochondrial membrane potential. In conclusion, the polyphenols all similarly prevented steatosis, ROS generation and iNOS induction, and protected against ER stress and mitochondrial impairment.